Fundamental Financial Ratios and Stock Prices: Panel Evidence from the Indonesia Stock Exchange - Yulianto, Dwi; Intan Purnama, Sri (Universitas Serang Raya, 2026)
Stock prices are often influenced by firms’ fundamental factors; however, empirical evidence on the impact of financial ratios on stock prices in emerging markets, including Indonesia, remains mixed. This study aims to analyze the effects of key financial ratios, Return on Assets (ROA), solvency ratios, Tobin’s Q, and the cash ratio, on the stock prices of non-financial firms listed on the Indonesia Stock Exchange (IDX) over the period 2018–2024. The study employs an unbalanced panel dataset drawn from the Osiris database, annual reports, and IDX publications, yielding a total of 3.121 firm-year observations after screening. The dependent variable is measured using the log of year-end stock prices, while the independent variables include lagged ROA, solvency indicators (DER, DAR, and interest coverage), lagged Tobin’s Q, and the cash ratio, with firm size and firm age as control variables. The analysis applies Generalized Least Squares (GLS) as the primary estimation method, complemented by Fixed Effects, Driscoll–Kraay, and System-GMM estimations to ensure robustness against heteroskedasticity, cross-sectional dependence, and dynamic endogeneity. The results show that ROA and Tobin’s Q exert a significant positive effect on stock prices, solvency exhibits a non-linear relationship consistent with trade-off theory, and the cash ratio demonstrates a positive but diminishing effect at excessive cash levels. These findings highlight the importance of fundamental financial ratios in shaping stock price formation in the Indonesian capital market, with practical implications for investment practices and corporate policy strategies.